Knowledge, attitude and practice toward epilepsy among mother with epilepsy children in pediatric clinic, Hospital Universiti Sains Malaysia - Mansor, Nur Shafieqa (Universiti Sains Malaysia, 2024)
Epilepsy is a chronic non-communicable disease of the brain that affects around 50 million people worldwide (WHO, 2023). The knowledge, attitude, and practice of mothers regarding epilepsy are crucial for the effective management of the condition, reducing stigma, providing emotional support, and ensuring the overall well-being of children with epilepsy. Objective of this study aims to determine the knowledge, attitude and practice toward epilepsy among mothers with epilepsy children in pediatric clinic, Hospital Universiti Sains Malaysia. Besides that, this study also investigates the association between knowledge and sociodemographic factors (education level) toward epilepsy among mothers with epilepsy children in pediatric clinic, Hospital Universiti Sains Malaysia. A cross-sectional study design was used, and 135 mothers participated in this research. The data was collected using a hard copy questionnaire distributed to the respondents. Descriptive statistics were used to describe the respondent and identify the level of knowledge, attitude, and practice toward epilepsy among mothers with epilepsy children in pediatric clinic, Hospital Universiti Sains Malaysia. Pearson Chi-square were used to test association between knowledge and sociodemographic factors (education level) toward epilepsy among mothers with epilepsy children in pediatric clinic, Hospital Universiti Sains Malaysia. The findings of the study revealed that most mothers (56.5%) have good knowledge about epilepsy, their overall attitude (84.4%) was neutral, and their practices (60.0%) during the last seizure were good. The results also showed no association between knowledge and educational level among mothers of children with epilepsy at the pediatric clinic, Hospital Universiti Sains Malaysia , where (p > 0.05). Although most of the mother has good knowledge and practice, however, their attitude toward epilepsy needs to be improved to enhance the care and support of their children.